Stock Market Response to Monetary Policy: Evidence from Iraq - Babela, Islam S.T.; Doski, Shivan A.M. (Ekonomika, 2023)
The current study seeks to assess the influence of monetary policy carried out by the Central Bank of Iraq (CBI henceforth) on stock market performance (SMP henceforth) from 2008 to 2021. Three monetary policy variables have been considered: money supply, inflation, and interest rate. Meanwhile, the number of transactions has measured the Iraqi Stock Exchange Market (ISX henceforth) performance. This study has used the Autoregressive Distributed Lag (ARDL henceforth) model by utilising monthly data. The results show that in the long term, the money supply and interest rates both have a negative impact on ISX performance. On the other hand, the findings have reported that inflation significantly and positively affects ISX performance. However, there was no indication of a relationship among the underlying variables in the short term. For investors and the appropriate authorities, these findings may have important implications.
Keywords: Monetary policy; Iraqi Stock Exchange; Stock Market Performance; ARDL model